Flame-retardant wear-resistant polyester fiber and preparation method thereof
Through the copolymerization spinning technology of nitrogen-phosphorus silicon modified silicon dioxide and PET polyester, a dense carbon layer structure is formed, which solves the problem of insufficient low oxygen index and wear resistance of polyester fibers, and achieves high flame retardant and wear resistance. The improvement of the mechanical properties has been enhanced.
Patent Information
- Application Number
- CN202411725790.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyester fiber has a low limit oxygen index, is prone to ignition and has insufficient wear resistance, which limits its widespread application. The existing flame retardants damage mechanical properties when improving flame retardant performance, and have poor wear resistance and durability.
Through the melt copolymerization spinning technology of nitrogen-phosphorus silicon-modified silicon dioxide copolyester and PET polyester, a dense carbon layer structure containing nitrogen-phosphorus silicon-containing synergistic flame retardant elements and nano-silicon dioxide is formed to improve flame retardant and wear resistance. performance.
It significantly improves the flame retardant and wear resistance of polyester fibers, forms an effective physical barrier, enhances its mechanical properties, avoids the peeling or breaking of the fibers during friction, and broadens the scope of application.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fibers, in particular to a flame-retardant and wear-resistant polyester fiber and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) fiber, commonly known as polyester fiber, is a widely used synthetic fiber. Due to its high output, good dimensional stability and wide range of applications, it is widely used in protective clothing, special work clothes, movie screens and various daily materials. However, the limiting oxygen index (LOI) of polyester fiber is relatively low, only about 20%, and it is a flammable fiber. At the same time, it is easy to produce a large amount of flammable substances when it is thermally decomposed, which is easy to ignite and cause fires. The molten droplets produced after combustion are easy to cause secondary combustion, which limits its wide application. In addition, in petrochemical, electric power, fire protection and other occasions with strict requirements on wear resistance, the wear resistance of polyester fiber still needs to be further improved. Therefore, the preparation of a polyester fiber that is both flame retardant and wear resistant has become a hot topic of current research.
[0003] Traditional additive flame retardants for polyester fibers mainly include inorganic flame retardants such as aluminum hydroxide, magnesium hydroxide, etc., which have good flame retardant effects, but are added in large amounts and are easy to agglomerate, which improves the flame retardant properties of the material while damaging its mechanical properties; there are also methods of coating the flame retardant on the surface of the fabric or infiltrating it into the fabric through a rolling or dipping process to improve its flame retardant properties. Although this method is simple to operate, the flame retardant is easy to migrate and precipitate, and the flame retardant effect is less durable; new flame retardants mainly include halogen-free and environmentally friendly flame retardants such as phosphorus-nitrogen flame retardants and silicon-based flame retardants. For example, the patent with patent number CN109912799B discloses a phosphorus-containing silicone flame retardant and its preparation and application. The prepared phosphorus-containing silicone flame retardant can better exert its silicon / phosphorus synergistic flame retardant effect, and can improve the flame retardant and smoke suppression properties of PET polyester materials, but does not significantly improve the wear resistance of PET materials.
[0004] Silicon dioxide has a high hardness, and its microparticles can fill tiny defects in the material, prevent microcracks from expanding, and form a hard protective layer on the surface of the material, thereby improving the wear resistance of the material; however, conventional nano-silicon dioxide is easy to agglomerate, and its wear resistance cannot be well exerted; in the prior art, high-speed stirring and ultrasonic dispersion are often used to temporarily disperse it evenly, but since the interaction force between nanoparticles is much stronger than the interaction force between nanoparticles and polymers, the dispersion effect is limited; the present invention aims to allow isocyanate monomers containing nitrogen, phosphorus and silicon flame retardant elements to form bonds with hydroxyl groups on the surface of silicon dioxide to eliminate the high energy potential on the surface, reduce agglomeration, and then condense with terephthalate to obtain a modified silicon dioxide copolyester with a structure similar to PET polyester, significantly improving the flame retardancy and wear resistance of polyester fibers and broadening their application range. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a flame-retardant and wear-resistant polyester fiber and a preparation method thereof, so that the prepared polyester fiber has high wear resistance, does not melt or shrink at high temperatures, and is not flammable, thereby preventing the fiber from peeling off or breaking during friction.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A method for preparing flame-retardant and wear-resistant polyester fiber comprises the following steps: Step 1: Under a nitrogen atmosphere, add dimethyl terephthalate, diol nitrogen phosphorus silicon modified silica, and ethylene glycol to a reactor, heat until the raw materials melt, raise the temperature to 200-220°C, react for 2-4 hours, then add antimony trioxide and triphenyl phosphate, raise the temperature to 250-270°C, react for 3-5 hours, cool to room temperature, and discharge under nitrogen pressure to obtain modified silica copolyester.
[0007] Step 2: Blend and extrude PET polyester chips, modified silica copolyester and antioxidant in a twin-screw extruder, the temperature of each section of the twin-screw extruder is 270-290°C, the screw speed is 70-90r / min, and then melt-spun on a spinning machine, and after winding and stretching, flame-retardant and wear-resistant polyester fibers are obtained.
[0008] Furthermore, in step 1, the ratio of dimethyl terephthalate, diol nitrogen phosphorus silicon modified silica, and ethylene glycol is 1 mol: (0.05-0.25) mol: (1.75-1.95) mol.
[0009] Furthermore, in step 2, the ratio of PET polyester chips, modified silica copolyester and antioxidant is 100g: (4-20)g: (0.4-0.8)g.
[0010] Furthermore, in step 2, the spinning temperature is 265-280° C., and the spinning speed is 800-1000 m / min.
[0011] Furthermore, the preparation method of nitrogen-phosphorus-silicon modified silicon dioxide in step 1 comprises the following steps: Step (1), under nitrogen atmosphere, add tris(hydroxymethyl)aminomethane hydrochloride and xylene to a reaction flask equipped with a thermometer, a reflux condenser and a fractionation device, stir evenly, add 3-isocyanate propyltrimethoxysilane, reflux at 135-150° C. for 5-12 hours until the distilled methanol reaches the theoretical amount, cool and crystallize, filter, wash with petroleum ether, and dry to obtain isocyanate methylamine cage ester. The preparation reaction formula is as follows:
[0012] Step (2), under nitrogen atmosphere, add chlorobis(4-methoxyphenyl)phosphine and N,N-dimethylformamide to a reaction flask equipped with a thermometer and a reflux condenser, stir evenly, add isocyanate methylamine cage ester and triethylamine, stir to react, after the reaction is completed, cool to room temperature, filter, wash with ethanol, and dry to obtain isocyanate nitrogen phosphorus silicon monomer. The preparation reaction formula is as follows:
[0013] Step (3), dispersing nano-silicon dioxide in toluene, ultrasonically dispersing for 20-40 minutes, adding the mixture to a reaction flask equipped with a thermometer and a reflux condenser, adding isocyanate nitrogen phosphorus silicon monomer and dibutyltin dilaurate, reacting at 70-90° C. for 3-8 hours, centrifuging at 3500-4500 r / min for 15-30 minutes, washing with toluene and ethanol alternately, then adding 20-35 g of boron tribromide and 200 mL of dichloromethane, reacting at 0-20° C. for 12-24 hours, and vacuum drying to obtain diol nitrogen phosphorus silicon modified silica.
[0014] Furthermore, in step (1), the ratio of tris(hydroxymethyl)aminomethane hydrochloride to 3-isocyanatepropyltrimethoxysilane is 1 mol:(1.05-1.2) mol.
[0015] Furthermore, in step (2), the ratio of chlorobis(4-methoxyphenyl)phosphine, isocyanate methylamine cage ester and triethylamine is 1 mol: (1.1-1.3) mol: (1.8-2.5) mol.
[0016] Furthermore, in step (2), the reaction temperature is 90-110° C. and the reaction time is 12-24 h.
[0017] Furthermore, in step (3), the ratio of nano-silicon dioxide, isocyanate-based nitrogen-phosphorus silicon monomer, dibutyltin dilaurate, and boron tribromide is 10 g: (0.02-0.1) g: (0.005-0.01) g: (20-35) g.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The invention uses tris(hydroxymethyl)aminomethane hydrochloride, chlorobis(4-methoxyphenyl)phosphine, silicon dioxide and the like as raw materials, obtains diol nitrogen phosphorus silicon modified silicon dioxide through chemical grafting reaction, then undergoes esterification polycondensation with dimethyl terephthalate, ethylene glycol and the like to obtain modified silicon dioxide copolyester, and finally undergoes melt copolymerization and spinning and drawing with PET polyester chips to obtain flame retardant and wear-resistant polyester fibers.
[0019] Modified silica copolyester contains nitrogen, phosphorus and silicon synergistic flame retardant elements. During the combustion process, organic silicon continuously migrates to the combustion surface and forms a ceramic carbon layer. Phosphorus-containing derivatives cover the polymer surface to isolate combustible gases. Nitrogen-containing substances can dilute combustible gases and prevent heat from transferring to the inside of the matrix, playing a condensed flame retardant role. The synergistic effect between the flame retardant elements and the dense carbon layer structure have a good insulation effect on combustible gases, oxygen and heat, forming an effective physical barrier and playing a good flame retardant role. After modification, nano-silica can stably exist in the polyester fiber matrix. Since silica has a high surface area and porosity, it can effectively increase the exchange interface of the flame retardant system, thereby improving the flame retardant effect. At the same time, the surface carbon layer formed can cover the decomposed polymer to prevent molten droplets from dripping, thereby achieving the effect of flame retardancy and anti-melting droplets.
[0020] Silica has small particles, large specific surface area and high hardness. Its microparticles can fill tiny defects in polyester fiber materials, prevent microcracks from expanding, and form a hard protective layer on the surface of the material, thereby improving the wear resistance of the material; the isocyanate group of the isocyanate nitrogen phosphorus silicon monomer can produce chemical bonds with the hydroxyl groups on the surface of silica, providing a good spatial stabilization effect for silica, making it difficult for particles to aggregate and bond, preventing the agglomeration of nano-silica, and making the prepared polyester fiber have good mechanical properties; when silica is evenly dispersed in the fiber, it can play a role similar to "microspheres", which can better absorb and disperse energy when subjected to external forces, and can more effectively resist wear, thereby enhancing wear resistance; silica can also form stable chemical bonds with the polyester fiber matrix to prevent the fiber from peeling off or breaking during friction, further improving the wear resistance of the fiber. DETAILED DESCRIPTION
[0021] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, without departing from the concept of the present invention, some adjustments and improvements can also be made, which all belong to the protection scope of the present invention.
[0022] The main raw material of the invention is tris(hydroxymethyl)aminomethane hydrochloride, with CAS number of 1185-53-1.
[0023] 3-Isocyanatopropyltrimethoxysilane 15396-00-6.
[0024] Chlorobis(4-methoxyphenyl)phosphine, CAS number is 13685-30-8. Example
[0025] (1) Under nitrogen atmosphere, 150 mmol of tris(hydroxymethyl)aminomethane hydrochloride and 300 mL of xylene were added to a reaction flask equipped with a thermometer, a reflux condenser and a fractionating device. After stirring evenly, 157.5 mmol of 3-isocyanatepropyltrimethoxysilane was added and the mixture was refluxed at 150°C for 5 h until the amount of methanol evaporated reached the theoretical amount. The mixture was cooled and crystallized, filtered, washed with petroleum ether and dried to obtain isocyanatemethylamine cage ester.
[0026] (2) Under a nitrogen atmosphere, 135 mmol of chlorobis(4-methoxyphenyl)phosphine and 1350 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring, 148.5 mmol of isocyanate methylamine cage ester and 243 mmol of triethylamine were added. The mixture was reacted at 110°C for 12 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain an isocyanate nitrogen phosphorus silicon monomer.
[0027] (3) Disperse 10 g of nano-silica in toluene, ultrasonically disperse for 30 min, add to a reaction flask equipped with a thermometer and a reflux condenser, add 0.02 g of isocyanate-based nitrogen-phosphorus-silicon monomer and 0.008 g of dibutyltin dilaurate, react at 80 °C for 5 h, centrifuge at 4000 r / min for 25 min, wash alternately with toluene and ethanol, then add 25 g of boron tribromide and 200 mL of dichloromethane, react at 100 °C for 16 h, and vacuum dry to obtain diol nitrogen-phosphorus-silicon modified silica.
[0028] (4) Under nitrogen atmosphere, 10 mmol of dimethyl terephthalate, 0.5 mmol of diol nitrogen phosphorus silicon modified silica, and 19.5 mmol of ethylene glycol were added to a reactor and heated until the raw materials melted. The temperature was raised to 210°C and the reaction was carried out for 3 h. Then, 0.03 mmol of antimony trioxide and 0.05 mmol of triphenyl phosphate were added, the temperature was raised to 260°C, the reaction was carried out for 4 h, and the reaction was cooled to room temperature. The material was discharged under nitrogen pressure to obtain modified silica copolyester.
[0029] (5) 100 g of PET polyester chips, 4 g of modified silica copolyester, and 0.6 g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 280°C and the screw speed was 80 r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 270°C and the spinning speed was 900 m / min. After winding and stretching, flame-retardant and wear-resistant polyester fibers were obtained. Example
[0030] (1) Under nitrogen atmosphere, add 220 mmol of tris(hydroxymethyl)aminomethane hydrochloride and 1100 mL of xylene to a reaction flask equipped with a thermometer, a reflux condenser and a fractionating device. After stirring evenly, add 231 mmol of 3-isocyanatepropyltrimethoxysilane and reflux at 135°C for 12 h until the evaporated methanol reaches the theoretical amount. Cool and crystallize, filter, wash with petroleum ether and dry to obtain isocyanate methylamine cage ester.
[0031] (2) Under a nitrogen atmosphere, 205 mmol of chlorobis(4-methoxyphenyl)phosphine and 1640 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring, 225.5 mmol of isocyanate methylamine cage ester and 369 mmol of triethylamine were added. The mixture was reacted at 110° C. for 12 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain an isocyanate nitrogen phosphorus silicon monomer.
[0032] (3) Disperse 10 g of nano-silica in toluene, ultrasonically disperse for 20 min, add to a reaction flask equipped with a thermometer and a reflux condenser, add 0.04 g of isocyanate-based nitrogen-phosphorus-silicon monomer and 0.005 g of dibutyltin dilaurate, react at 90 °C for 3 h, centrifuge at 4500 r / min for 15 min, wash alternately with toluene and ethanol, then add 20 g of boron tribromide and 200 mL of dichloromethane, react at 20 °C for 12 h, and vacuum dry to obtain diol nitrogen-phosphorus-silicon modified silica.
[0033] (4) Under nitrogen atmosphere, 10 mmol of dimethyl terephthalate, 1 mmol of diol nitrogen phosphorus silicon modified silica, and 19 mmol of ethylene glycol were added to a reactor and heated until the raw materials melted. The temperature was raised to 220°C and the reaction was carried out for 2 h. Then, 0.03 mmol of antimony trioxide and 0.05 mmol of triphenyl phosphate were added, the temperature was raised to 270°C, the reaction was carried out for 3 h, and the reaction was cooled to room temperature. The material was discharged under nitrogen pressure to obtain modified silica copolyester.
[0034] (5) 100 g of PET polyester chips, 8 g of modified silica copolyester, and 0.4 g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 290°C and the screw speed was 90 r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 280°C and the spinning speed was 1000 m / min. After winding and stretching, flame-retardant and wear-resistant polyester fibers were obtained. Example
[0035] (1) Under nitrogen atmosphere, add 80 mmol of tris(hydroxymethyl)aminomethane hydrochloride and 425 mL of xylene to a reaction flask equipped with a thermometer, a reflux condenser and a fractionating device. After stirring evenly, add 96 mmol of 3-isocyanatepropyltrimethoxysilane and reflux at 135°C for 12 h until the amount of methanol evaporated reaches the theoretical amount. Cool and crystallize, filter, wash with petroleum ether and dry to obtain isocyanate methylamine cage ester.
[0036] (2) Under a nitrogen atmosphere, add 75 mmol of chlorobis(4-methoxyphenyl)phosphine and 900 mL of N,N-dimethylformamide to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, add 97.5 mmol of isocyanate methylamine cage ester and 187.5 mmol of triethylamine. React at 90 °C for 24 h, cool to room temperature, filter, wash with ethanol, and dry to obtain isocyanate nitrogen phosphorus silicon monomer.
[0037] (3) Disperse 10 g of nano-silica in toluene, ultrasonically disperse for 40 min, add to a reaction flask equipped with a thermometer and a reflux condenser, add 0.06 g of isocyanate-based nitrogen-phosphorus-silicon monomer and 0.01 g of dibutyltin dilaurate, react at 70 °C for 8 h, centrifuge at 3500 r / min for 30 min, wash alternately with toluene and ethanol, then add 35 g of boron tribromide and 200 mL of dichloromethane, react at 0 °C for 24 h, and vacuum dry to obtain diol nitrogen-phosphorus-silicon modified silica.
[0038] (4) Under nitrogen atmosphere, 10 mmol of dimethyl terephthalate, 1.5 mmol of diol nitrogen phosphorus silicon modified silica, and 18.5 mmol of ethylene glycol were added to a reactor and heated until the raw materials melted. The temperature was raised to 200°C and the reaction was carried out for 4 h. Then, 0.03 mmol of antimony trioxide and 0.05 mmol of triphenyl phosphate were added, the temperature was raised to 250°C, the reaction was carried out for 5 h, and the reaction was cooled to room temperature. The material was discharged under nitrogen pressure to obtain modified silica copolyester.
[0039] (5) 100 g of PET polyester chips, 12 g of modified silica copolyester, and 0.8 g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 270°C and the screw speed was 70 r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 265°C and the spinning speed was 800 m / min. After winding and stretching, flame-retardant and wear-resistant polyester fibers were obtained. Example
[0040] (1) Under nitrogen atmosphere, add 25 mmol of tris(hydroxymethyl)aminomethane hydrochloride and 100 mL of xylene to a reaction flask equipped with a thermometer, a reflux condenser and a fractionating device. After stirring evenly, add 28 mmol of 3-isocyanatepropyltrimethoxysilane and reflux at 145°C for 8 h until the evaporated methanol reaches the theoretical amount. Cool and crystallize, filter, wash with petroleum ether and dry to obtain isocyanate methylamine cage ester.
[0041] (2) Under a nitrogen atmosphere, add 20 mmol of chlorobis(4-methoxyphenyl)phosphine and 185 mL of N,N-dimethylformamide to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, add 25 mmol of isocyanate methylamine cage ester and 40 mmol of triethylamine. The mixture is reacted at 105 °C for 18 h. The mixture is cooled to room temperature, filtered, washed with ethanol, and dried to obtain an isocyanate nitrogen phosphorus silicon monomer.
[0042] (3) Disperse 10 g of nano-silica in toluene, ultrasonically disperse for 35 min, add to a reaction flask equipped with a thermometer and a reflux condenser, add 0.08 g of isocyanate-based nitrogen-phosphorus-silicon monomer and 0.006 g of dibutyltin dilaurate, react at 85 °C for 7 h, centrifuge at 4200 r / min for 25 min, wash alternately with toluene and ethanol, then add 30 g of boron tribromide and 200 mL of dichloromethane, react at 5 °C for 16 h, and vacuum dry to obtain diol nitrogen-phosphorus-silicon modified silica.
[0043] (4) Under nitrogen atmosphere, 10 mmol of dimethyl terephthalate, 2 mmol of diol nitrogen phosphorus silicon modified silica, and 18 mmol of ethylene glycol were added to a reactor and heated until the raw materials melted. The temperature was raised to 205°C and the reaction was carried out for 3 h. Then, 0.03 mmol of antimony trioxide and 0.05 mmol of triphenyl phosphate were added, the temperature was raised to 265°C, the reaction was carried out for 5 h, and the reaction was cooled to room temperature. The material was discharged under nitrogen pressure to obtain modified silica copolyester.
[0044] (5) 100 g of PET polyester chips, 16 g of modified silica copolyester, and 0.7 g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 275°C and the screw speed was 85 r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 270°C and the spinning speed was 950 m / min. After winding and stretching, flame-retardant and wear-resistant polyester fibers were obtained. Example
[0045] (1) Under nitrogen atmosphere, add 60 mmol of tris(hydroxymethyl)aminomethane hydrochloride and 210 mL of xylene to a reaction flask equipped with a thermometer, a reflux condenser and a fractionating device. After stirring evenly, add 68.5 mmol of 3-isocyanatepropyltrimethoxysilane and reflux at 145°C for 10 h until the evaporated methanol reaches the theoretical amount. Cool and crystallize, filter, wash with petroleum ether and dry to obtain isocyanate methylamine cage ester.
[0046] (2) Under a nitrogen atmosphere, 50 mmol of chlorobis(4-methoxyphenyl)phosphine and 500 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 62.5 mmol of isocyanate methylamine cage ester and 112.5 mmol of triethylamine were added. The mixture was reacted at 105 °C for 15 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain an isocyanate nitrogen phosphorus silicon monomer.
[0047] (3) Disperse 10 g of nano-silica in toluene and ultrasonically disperse for 35 min. Add the mixture into a reaction flask equipped with a thermometer and a reflux condenser. Add 0.1 g of isocyanate-based nitrogen-phosphorus-silicon monomer and 0.009 g of dibutyltin dilaurate. React at 85 °C for 8 h. Centrifuge at 4000 r / min for 30 min. Wash with toluene and ethanol alternately. Then add 32 g of boron tribromide and 200 mL of dichloromethane. React at 0 °C for 24 h. Dry in vacuo to obtain diol nitrogen-phosphorus-silicon modified silica.
[0048] (4) Under nitrogen atmosphere, 10 mmol of dimethyl terephthalate, 2.5 mmol of diol nitrogen phosphorus silicon modified silica, and 17.5 mmol of ethylene glycol were added to a reactor and heated until the raw materials melted. The temperature was raised to 220°C and the reaction was carried out for 3 h. Then, 0.03 mmol of antimony trioxide and 0.05 mmol of triphenyl phosphate were added, the temperature was raised to 265°C, the reaction was carried out for 4 h, and the reaction was cooled to room temperature. The material was discharged under nitrogen pressure to obtain modified silica copolyester.
[0049] (5) 100 g of PET polyester chips, 20 g of modified silica copolyester, and 0.8 g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 280°C and the screw speed was 90 r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 275°C and the spinning speed was 850 m / min. After winding and stretching, flame-retardant and wear-resistant polyester fibers were obtained.
[0050] Comparative Example 1 (1) 10 g of isocyanate nitrogen phosphorus silicon monomer (prepared in Example 1), 25 g of boron tribromide and 200 mL of dichloromethane were added to a reaction flask, reacted at 100° C. for 16 h, and vacuum dried to obtain a diol nitrogen phosphorus silicon monomer.
[0051] (2) Under nitrogen atmosphere, 10 mmol of dimethyl terephthalate, 0.5 mmol of diol nitrogen-phosphorus-silicon monomer, and 19.5 mmol of ethylene glycol were added to a reactor and heated until the raw materials melted. The temperature was raised to 210°C and the reaction was continued for 3 h. Then, 0.03 mmol of antimony trioxide and 0.05 mmol of triphenyl phosphate were added, the temperature was raised to 260°C, the reaction was continued for 4 h, and the reaction was continued to cool to room temperature. The material was discharged under nitrogen pressure to obtain nitrogen-phosphorus-silicon modified copolyester.
[0052] (3) 100 g of PET polyester chips, 4 g of nitrogen-phosphorus-silicon modified copolyester, and 0.6 g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 280°C and the screw speed was 80 r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 270°C and the spinning speed was 900 m / min. After winding and drawing, flame-retardant polyester fibers were obtained.
[0053] Comparative Example 2 100g of PET polyester chips, 4g of nano-silicon dioxide and 0.6g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 280°C and the screw speed was 80r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 270°C and the spinning speed was 900m / min. After winding and stretching, polyester fibers were obtained.
[0054] Comparative Example 3 100g of PET polyester chips and 0.6g of antioxidant 1010 were blended and extruded in a twin-screw extruder. The temperature of each section of the twin-screw extruder was 280°C and the screw speed was 80r / min. Then, they were melt-spun on a spinning machine. The spinning temperature was 270°C and the spinning speed was 900m / min. After winding and stretching, polyester fibers were obtained.
[0055] Limiting oxygen index (LOI) test: refer to FZ / T 50017-2011 "Polyester fiber flame retardant test method oxygen index method", use oxygen index tester to test the limiting oxygen index. Before the test, weigh about 0.3g of prepared polyester fiber sample, use yarn length measuring instrument to twist the fiber sample, the twist is between 110-150 twists / m, then fold it in the middle into strands, fix the fiber end and then test.
[0056] Vertical burning grade (UL-94 grade) test: According to ASTM D3801-2010 "Standard test method for measuring comparative burning characteristics of solid plastics in a vertical position", the vertical burning performance of flame-retardant PET samples is tested using a UL94 burning test chamber. The test specimen size is the same as the limiting oxygen index test specimen.
[0057] Table 1 Flame retardant performance test LOI (%) UL-94 Rating Whether to ignite the absorbent cotton Example 1 25.5 V-1 no Example 2 26.2 V-0 no Example 3 29.1 V-0 no Example 4 31.4 V-0 no Example 5 32.0 V-0 no Comparative Example 1 24.6 V-1 no Comparative Example 2 22.3 V-2 yes Comparative Example 3 18.3 V-2 yes It can be seen from the test results in the above table that with the increase of the content of modified silica copolyester, the flame retardant properties of polyester fiber are gradually enhanced, and the flame retardant material level is reached in the embodiments. This is because, on the one hand, after modification, nano-silicon dioxide can be stably present in the polyester fiber matrix. Since silica has a high specific surface area and porosity, it can effectively increase the exchange interface of the flame retardant system, thereby improving the flame retardant effect. At the same time, the surface carbon layer formed can cover the decomposed polymer to prevent the molten droplets from dripping, thereby achieving the flame retardant and anti-melting droplet effect; on the other hand, the modified silica copolyester contains nitrogen, phosphorus and silicon synergistic flame retardant elements. Silicone continuously migrates to the combustion surface during the combustion process and forms a ceramic carbon layer. Phosphorus derivatives cover the polymer surface to isolate combustible gases. Nitrogen-containing substances can dilute combustible gases and prevent heat from transferring to the inside of the matrix, playing a condensed flame retardant role. The synergistic effect between the flame retardant elements and the dense carbon layer structure have a good isolation effect on combustible gases, oxygen and heat, forming an effective physical barrier and playing a good flame retardant role. Comparative Example 1 does not contain nano-silicon dioxide, but contains nitrogen, phosphorus and silicon synergistic flame retardant elements, and has good flame retardant properties; Comparative Example 2 contains nano-silicon dioxide, but has not been modified, has poor dispersion performance in the polyester fiber matrix, and has poor flame retardant properties; Comparative Example 3 is pure polyester fiber and does not have flame retardant properties.
[0058] Wear resistance test: adopt Y731 type cohesion force meter, adopt uniform speed friction, when start the test, the counter starts counting automatically, use the friction plate to test the friction effect of the fiber, when the yarn is worn off and the machine stops, the data displayed on the counter is the number of times the fiber is worn, and the test is carried out at room temperature; the test conditions are: static tension is 100cN, self-pressure of the grinding plate is 2.35N, no-load reciprocating speed of the grinding plate is 143 times / min, a total of 30 tests are conducted, and the average value is taken.
[0059] Table 2 Wear resistance test Average wear times (times) Example 1 99 Example 2 108 Example 3 124 Example 4 139 Example 5 146 Comparative Example 1 52 Comparative Example 2 70 Comparative Example 3 51 It can be seen from the test results in the above table that with the increase of the content of modified silica copolyester, the wear resistance of the polyester fiber is gradually enhanced, and the wear resistance number of Example 5 reaches 146 times. This is because on the one hand, the silica particles are small, the specific surface area is large, and the hardness is high. Its microparticles can fill the tiny defects in the polyester fiber material, prevent the microcracks from expanding, and form a hard protective layer on the surface of the material, thereby improving the wear resistance of the material; on the other hand, when silica is evenly dispersed in the fiber, it can play a role similar to "microspheres", which can better absorb and disperse energy when subjected to external forces, and can more effectively resist wear, thereby enhancing wear resistance. Silica can also form a stable chemical bond with the polyester fiber matrix to prevent the fiber from peeling off or breaking during friction, further improving the wear resistance of the fiber.
[0060] Mechanical properties test: The mechanical properties of the fiber were tested using a multifilament strength and elongation tester with a clamping length of 200 mm, a tensile rate of 200 mm / min, a pre-tension of 5 cN, and 20 measurements per group of fibers to take the average value.
[0061] Table 3 Mechanical properties test Breaking strength (cN / dtex) Example 1 1.68 Example 2 1.96 Example 3 2.34 Example 4 2.52 Example 5 2.58 Comparative Example 1 1.45 Comparative Example 2 1.33 Comparative Example 3 1.25 The isocyanate group of the isocyanate nitrogen phosphorus silicon monomer can produce a chemical bond with the hydroxyl group on the surface of silica, so that the prepared nitrogen phosphorus silicon flame retardant can be firmly embedded in the surface of silica, providing a good spatial stabilization effect for silica, making it difficult for particles to aggregate and bond, preventing the agglomeration of nano-silica, and making the prepared polyester fiber have good mechanical properties.
[0062] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing flame-retardant and wear-resistant polyester fiber, characterized in that: The preparation method comprises the following steps: Step 1: Under a nitrogen atmosphere, add dimethyl terephthalate, diol nitrogen phosphorus silicon modified silica, and ethylene glycol into a reactor, heat until the raw materials melt, raise the temperature to 200-220°C, react for 2-4 hours, then add antimony trioxide and triphenyl phosphate, raise the temperature to 250-270°C, react for 3-5 hours, cool to room temperature, and discharge under nitrogen pressure to obtain modified silica copolyester; Step 2: Blend and extrude PET polyester chips, modified silica copolyester and antioxidant in a twin-screw extruder, the temperature of each section of the twin-screw extruder is 270-290°C, the screw speed is 70-90r / min, and then melt-spun on a spinning machine, and after winding and stretching, flame-retardant and wear-resistant polyester fibers are obtained.
2. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 1, characterized in that: In the step 1, the ratio of dimethyl terephthalate, diol nitrogen phosphorus silicon modified silica, and ethylene glycol is 1 mol: (0.05-0.25) mol: (1.75-1.95) mol.
3. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 1, characterized in that: In the step 2, the ratio of PET polyester chips, modified silica copolyester and antioxidant is 100g: (4-20)g: (0.4-0.8)g.
4. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 1, characterized in that: In the step 2, the spinning temperature is 265-280° C., and the spinning speed is 800-1000 m / min.
5. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 1, characterized in that: The preparation method of nitrogen-phosphorus-silicon modified silicon dioxide in step 1 comprises the following steps: Step (1), under a nitrogen atmosphere, add tris(hydroxymethyl)aminomethane hydrochloride and xylene to a reaction flask equipped with a thermometer, a reflux condenser and a fractionation device, stir evenly, add 3-isocyanatepropyltrimethoxysilane, reflux at 135-150° C. for 5-12 h until the distilled methanol reaches the theoretical amount, cool and crystallize, filter, wash with petroleum ether, and dry to obtain isocyanate methylamine cage ester; Step (2), under a nitrogen atmosphere, add chlorobis(4-methoxyphenyl)phosphine and N,N-dimethylformamide to a reaction flask equipped with a thermometer and a reflux condenser, stir evenly, add isocyanate methylamine cage ester and triethylamine, stir to react, and after the reaction is completed, cool to room temperature, filter, wash with ethanol, and dry to obtain an isocyanate nitrogen phosphorus silicon monomer; Step (3), dispersing nano-silicon dioxide in toluene, ultrasonically dispersing for 20-40 minutes, adding the nano-silicon dioxide into a reaction flask equipped with a thermometer and a reflux condenser, adding isocyanate nitrogen phosphorus silicon monomer and dibutyltin dilaurate, reacting at 70-90° C. for 3-8 hours, centrifuging at 3500-4500 r / min for 15-30 minutes, washing with toluene and ethanol alternately, then adding boron tribromide and dichloromethane, reacting at 0-20° C. for 12-24 hours, and vacuum drying to obtain diol nitrogen phosphorus silicon modified silicon dioxide.
6. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 5, characterized in that: In the step (1), the ratio of tris(hydroxymethyl)aminomethane hydrochloride to 3-isocyanatepropyltrimethoxysilane is 1 mol: (1.05-1.2) mol.
7. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 5, characterized in that: In the step (2), the ratio of chlorobis(4-methoxyphenyl)phosphine, isocyanate methylamine cage ester and triethylamine is 1 mol: (1.1-1.3) mol: (1.8-2.5) mol.
8. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 5, characterized in that: In the step (2), the reaction temperature is 90-110° C. and the reaction time is 12-24 h.
9. The method for preparing the flame-retardant and wear-resistant polyester fiber according to claim 5, characterized in that: In the step (3), the ratio of nano-silicon dioxide, isocyanate-based nitrogen-phosphorus silicon monomer, dibutyltin dilaurate, and boron tribromide is 10 g: (0.02-0.1) g: (0.005-0.01) g: (20-35) g.
10. A flame retardant and wear-resistant polyester fiber, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Flame retardant copolyetheresters
CA1254332A
Phosphorus-containing PTT fire-resistant copolyesters / nano composite material and preparation method thereof
CN101709137A
Phosphorous-nitrogen-containing polyethylene glycol terephthalate flame retardant copolyester and application of flame retardant copolyester
CN104387571A
Polysiloxane fire retardant containing nitrogen, phosphorus and silicon, and preparation method thereof
CN106700081A
High-temperature-resistant flame-retardant fabric and preparation method thereof
CN116240666A
